1993
DOI: 10.1002/j.1460-2075.1993.tb05785.x
|View full text |Cite
|
Sign up to set email alerts
|

Silencers in abdominal-B, a homeotic Drosophila gene.

Abstract: Homeotic genes determine the developmental fates of cells. Restriction of their expression along the body axis is of prime importance for normal development. We searched for cis‐regulatory sequences within Abdominal‐B (Abd‐B), a homeotic Drosophila gene, by testing genomic Abd‐B fragments for their ability to confer beta‐galactosidase (beta‐gal) expression in transformed embryos. One of the Abd‐B fragments, called IAB5, mediates a beta‐gal pattern restricted along the body axis to the Abd‐B expression domain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 63 publications
(115 reference statements)
4
129
0
Order By: Relevance
“…We have evidence that, at the endogenous locus, the IAB5 enhancer in fact is recruited selectively only to the AbdB promoter by a tethering mechanism (R.A.D., unpublished data). In addition, all of the existing data indicate that the iab enhancers are active only later in development, when they begin to direct expression of the neighboring homeotic genes (4,16,17,36). However, we cannot discount the possibility that the intergenic transcription is directed by existing or as yet unknown enhancers in the BX-C.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…We have evidence that, at the endogenous locus, the IAB5 enhancer in fact is recruited selectively only to the AbdB promoter by a tethering mechanism (R.A.D., unpublished data). In addition, all of the existing data indicate that the iab enhancers are active only later in development, when they begin to direct expression of the neighboring homeotic genes (4,16,17,36). However, we cannot discount the possibility that the intergenic transcription is directed by existing or as yet unknown enhancers in the BX-C.…”
Section: Discussionmentioning
confidence: 86%
“…In this way, cis-regulatory elements within the separate domains are able to direct expression of abdA and AbdB in specific abdominal segments of the Drosophila embryo. Indeed, transgenic studies have identified enhancers from the iab8 (IAB8) (4), iab7 (IAB7) (4), and iab5 (IAB5) (16,17) regions that drive expression in specific abdominal segments. Furthermore, elements capable of silencing gene transcription, Polycomb response elements, have been discovered in the iab8 (4), iab7 (10,18), and iab5 regions (17,19).…”
Section: E Xpression Of the Abdominal-a (Abda) And Abdominal-b (Abdb)mentioning
confidence: 99%
See 1 more Smart Citation
“…Pc-G proteins bind to specific regulatory regions. so-called Pc-G response elements (PREs), which are necessary for maintaining the repressed state of homeotic genes (Miiller and Bienz 1991;Busturia and Bienz 1993;Simon et al 1993;Chan et al 1994;Chiang et al 1995). Little is known, however, about how Pc-G proteins interact molecularly or how they acquire PRE binding site specificity.…”
mentioning
confidence: 99%
“…S11 in the supplementary material). The IAB5 enhancer (Busturia and Bienz, 1993) activates lacZ expression in the presumptive abdomen (Fig. 5A), but fails to activate white (Fig.…”
Section: Research Articlementioning
confidence: 99%